Management consultancy in Singapore : from the supply and demand perspective. - Choo, Boon Kuan. (2013)
The Straits Times reported that the Singapore government is encouraging local SMEs to develop towards Asian MNCs status. This is timely because as the Singapore economy matures, local enterprises need to grow in tandem with the economy to progress and maximize their gains. To become Asian MNCs, companies need to acquire new management techniques and ways of implementing them. In this aspect, the expanding companies will not only face problems due to their own limitations, but also other difficulties which come about when they venture abroad into the realm of the unknown. In response to these emerging problems, it is appropriate that the companies engage the services of management consultants who are experts in the area of change management.